Increasing Website Traffic with the On-Page Search Engine Optimization Approach: A Case Study of LaskarKoinSeribu.org - Jihadi, Hilman; Dade Maulana; Aryanti Kristantini (Indonesian Scientific Publication, 2025)
This study aims to increase traffic to the LaskarKoinSeribu.org website, an Islamic-based donation platform, through the implementation of On-Page SEO strategies. A comprehensive analysis identified several key issues, including low organic traffic, suboptimal keyword usage, less SEO-friendly URL structures, inadequate content optimization, and weak internal linking. To address these challenges, this study utilizes various SEO tools such as Google Keyword Planner, Semrush, and Meta Tags Analyzer to design strategies based on targeted keywords, including